Financial report readability and accounting conservatism - Zhimin Yu (Journal of Risk and Financial Management, 2022)
Accounting conservatism could affect the quantitative information on a financial statement. In this paper, the author focuses on qualitative information on financial statements. The author investigates the association between financial report readability and accounting conservatism and uses the FOG index to measure financial report readability. By using management discussion and analysis (MD&A) from 1996 to 2019, the author finds that financial report readability is positively associated with accounting conservatism. Additionally, the author separates the samples into high-compensation incentive and low-compensation incentive subsamples. The results show that the above association is stronger in the high-compensation incentive samples than in the low-compensation incentive samples. This result implies that accounting conservatism could mitigate managerial opportunism in the qualitative disclosure setting.
Keywords: 650; financial report readability; accounting conservatism; compensation incentive